A new model for correlation and prediction of equilibrium CO2 solubility in N‐methyl‐4‐piperidinol solvent. Issue 8 (23rd March 2017) - Xiao, Min; Cui, Ding; Liu, Helei; Tontiwachwuthikul, Paitoon; Liang, Zhiwu
Abstract : In this work, the equilibrium CO2 solubility in the aqueous tertiary amine, N‐methyl‐4‐piperidinol (MPDL) was measured over a range of temperatures, CO2 partial pressures and amine concentrations. The dissociation constant of the MPDL solution was determined as well. A new thermodynamic model was developed to predict the equilibrium CO2 solubility in the MPDL‐H2 O‐CO2 system. This model, equipped with the correction factor (Cf ), can give reasonable prediction with an average absolute deviation of 2.0%, and performs better than other models (i.e., KE model, Li‐Shen model, and Hu‐Chakma). The second‐order reaction rate constant (k2 ) of MPDL and the heat of CO2 absorption (–ΔHabs ) into aqueous MPDL solutions were evaluated as well. Based on the comparison with some conventional amines, MPDL revealed a high‐equilibrium CO2 loading, reasonably fast absorption rate when compared with other tertiary amines, and a low energy requirement for regeneration. It may, therefore, be considered to be an alternative solvent for CO2 capture. © 2017 American Institute of Chemical Engineers AIChE J, 63: 3395–3403, 2017